Three new species of Lernanthropus (Copepoda: Siphonostomatoida) from Vietnam - Kovaleva, Nina N. (Zootaxa, 2025)
Three new species of copepods of the genus Lernanthropus de Blainville, 1822 (Siphonostomatoida: Lernanthropidae) parasitic on marine fishes of Vietnam are described and illustrated: Lernanthropus hexodonis Kovaleva, sp. nov., L. kazachenkoi Kovaleva, sp. nov., and L. marginatus Kovaleva, sp. nov.